2015
DOI: 10.3109/01676830.2015.1078378
|View full text |Cite
|
Sign up to set email alerts
|

The Learning Curve in Endoscopic Dacryocystorhinostomy: Outcomes in Surgery Performed by Trainee Oculoplastic Surgeons

Abstract: Good surgical outcomes are achievable training in en-DCR surgery. Adequate operating time needs to be planned. Failure was primarily due to closure of the soft-tissue ostium, either secondary to inadequate osteotomy and sac-marsupialisation or postoperative scarring. Intra-operative mucosal trauma is higher amongst trainees and adjuvant silicone stenting during the training period may be of value where mucosal adhesions are anticipated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…[4] To the best of our knowledge, there are five previous reports on experiences of trainees with DCR, two studies that have focused on external DCR and three on En-DCR. [1011121314] Two studies with endoscopic DCR involved otolaryngology fellows and consultants and only one study involved ophthalmology trainees. This study documents the clinical profile, intraoperative details, postoperative ostium findings, and surgical outcomes after endoscopic En-DCR operated by ophthalmic plastic surgery fellow during the training period with good success rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[4] To the best of our knowledge, there are five previous reports on experiences of trainees with DCR, two studies that have focused on external DCR and three on En-DCR. [1011121314] Two studies with endoscopic DCR involved otolaryngology fellows and consultants and only one study involved ophthalmology trainees. This study documents the clinical profile, intraoperative details, postoperative ostium findings, and surgical outcomes after endoscopic En-DCR operated by ophthalmic plastic surgery fellow during the training period with good success rates.…”
Section: Discussionmentioning
confidence: 99%
“…appears to be comparable. [14] In their study, three different trainees operated on 17, 8, and 13 cases each, and the mean surgical time in the operating room was 95.7 ± 27.3 min. While in principle, the surgical technique is by and large similar to our technique, it is worth noting that in their cohort, five cases required septoplasty, which was done simultaneously by the preceptor.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the separation of their groups into cases done by consultants and trainees was artificial and did not reflect the reality of surgical practice. Malhotra et al (2015) reported the results of 38 cases of endonasal DCR independently performed by 3 trainee (all post -residency) oculoplasty surgeons, where all trainees underwent a supervised training and were allowed to operate independently only after a minimum of 6 months of fellowship training. They excluded the cases prior to being independent, thus excluding the learning curve.…”
Section: Discussionmentioning
confidence: 99%
“…Mirza et al (2002) found an improved outcome in the last 38 cases of endonasal DCR out of a total of 76 cases but did not explicitly mention data documenting the learning curve. Surprisingly, no study till date has evaluated the learning curve in detail (Mirza et al, 2002;Pandya et al, 2010;Malhotra, 2015;Kashkouli et al, 2003). Ours was a unique study in which we compared the results of external DCR surgery by a trainee ophthalmologist over time.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have reported success rates as low as 57%, while others have reported success rates of 100%. [4][5][6] A recent retrospective review of 1083 END-DCRs performed by a single surgeon reported a success rate of 92.7%. 7 The reasons for this variation are unclear but probably include differences in patient selection, exact surgical approach, surgeon experience, time to follow-up, and definition of 'success'.…”
Section: Introductionmentioning
confidence: 99%